DEVELOPING MOODLE-BASED E-LEARNING MEDIA TO LEARN NEWS WRITING - Aswadi Jaya; Asti Veto Mortini (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2023)
Students majoring in English language education need to have proficient writing skills which show wide range of cognitive and linguistics abilities. For that reason, news writing that includes techniques for writing good headlines, techniques for writing interesting headlines, and techniques for creating a comprehensive and in-depth news body is appropriate to facilitate that needs. The purpose of this research is to develop Moodle, Google Slides, and Power Point-based E-Learning aids for learning how to write news articles in writing for mass media course for English language education students. This study employs the 4D development model (Define, Design, Development, and Dissemination) to conduct R&D. This research uses a non-test instrument data collection strategy in the form of a questionnaire distributed to two material experts and two media experts. The results are as follows: a) the validation results by material experts received a score of 81.54 %, placing them in the very feasible category; b) the validation results by media experts received a score of 78.4 %, placing them in the feasible category. These results indicate that the E-Learning Moodle's learning materials are suitable to be used in the journalism course